Conserved principles of the pluripotency and primordial germ cell gene regulatory networks: from basal vertebrates to mammals - Simpson, Luke Alexander (2022)
Pluripotency defines the unlimited potential of cells in the primitive ectoderm of vertebrate embryos, from which all adult somatic cells and germ cells are derived. Understanding how the programming of pluripotency evolved has been obscured by the study of early development in models from lower vertebrates in which pluripotency is not conserved. Using Axolotl to model the development of the tetrapod ancestor, I examined the role of two transcription factors in early development associated with pluripotency in human embryonic stem cells (hESC), NANOG and ELK1.